Effect of Qmix 2in1, chlorhexidine gluconate, and ethylenediaminetetraacetic acid on postoperative pain after root canal treatment: A double-blind randomized clinical trial - Selen İnce Yusufoğlu; Keziban Olcay (Tabriz University of Medical Sciences, 2022)
Background. This study aimed to investigate the effects of different final irrigation solutions on postoperative pain following root canal treatment. Methods. Eighty-nine nonvital premolar and molar teeth with periapical lesions (PAI: 3‒4) without any clinical symptoms were included. The patients were randomly assigned to three groups according to the final irrigation solutions used: G1: 2 mL of Qmix (n=29), G2: 2 mL of 17% ethylenediaminetetraacetic acid (EDTA) (n=30), and G3: 2 mL of 2% chlorhexidine gluconate (CHX) (n=30). All the patients were prescribed 100 mg of flurbiprofen to use as needed for pain. The patients were asked to rate their pain status according to the verbal rating scale at 12, 24, 48, and 72 hours, and one week. The data were analyzed using Pearson's chi-squared test, Fisher's exact test, and chi-squared analysis with Monte Carlo simulation. The significance level was set at P≤0.05. Results. No significant differences were observed in postoperative pain rates at 12, 48, and 72 hours and one week (P>0.05). However, in the Qmix group, a significantly lower pain level was observed at 24 hours with EDTA and CHX (P=0.019). The rate of mild pain in the EDTA group at 72 hours (18.8%) was significantly higher in premolar teeth than in molar teeth (P=0.012). The moderate pain level in the EDTA group at 12 hours was significantly higher in those>60 years of age (P=0.008). Conclusion. The use of Qmix as an irrigation solution resulted in lower postoperative pain levels at 24 hours compared to other solutions. Therefore, Qmix can be considered a proper final irrigation solution in endodontic treatment regarding postoperative pain.